2024
DOI: 10.1037/sgd0000589
|View full text |Cite
|
Sign up to set email alerts
|

Parent responses to their sexual and gender minority children: Implications for parent-focused supportive interventions.

Abstract: Parental acceptance is a robust protective mechanism against poor mental health in sexual and gender minority (SGM) youth. Yet, little work has examined how parent-focused interventions could increase parental support of SGM youth while simultaneously reducing parental rejection. To inform parenting intervention content and strategies for parental engagement in such interventions, this mixed-methods study examined how non-SGM parents of SGM youth (N = 205) qualitatively described their relationship with their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…Lower Akaike Information Criteria and Bayesian Information Criteria and higher R-squared values indicated that, for both anxiety and depression, Step 3 models (with all Stigma Experiences subscales added together with covariates) were the optimally fitting models. There was no evidence of multicollinearity based on an eigensystem analysis of covariance comparison (Belsley et al, 1980;Schreiber-Gregory, 2017).…”
Section: Associations Between Parents' Stigma Experiences and Anxiety...mentioning
confidence: 89%
See 1 more Smart Citation
“…Lower Akaike Information Criteria and Bayesian Information Criteria and higher R-squared values indicated that, for both anxiety and depression, Step 3 models (with all Stigma Experiences subscales added together with covariates) were the optimally fitting models. There was no evidence of multicollinearity based on an eigensystem analysis of covariance comparison (Belsley et al, 1980;Schreiber-Gregory, 2017).…”
Section: Associations Between Parents' Stigma Experiences and Anxiety...mentioning
confidence: 89%
“…The SPACES study was approved by the University of Maryland Institutional Review Board. Previous research drawing upon the SPACES study sample has reported upon parents’ explicit and implicit acceptance and rejection toward their SGM child and associations with child mental health (Clark et al, 2022; Hubachek et al, 2023) as well as parents’ perspectives on supportive intervention content for parents of SGM youth (Seager van Dyk et al, 2022).…”
Section: Methodsmentioning
confidence: 99%
“…Taken together, our findings underscore the pressing need for targeted interventions for SGM youth, who are at increased risk for depression and other mental health issues. Family support emerged as a critical variable that is likely to influence clinical- and mood-related outcomes, underscoring the well-researched need for family-based interventions in bolstering SGM youth mental health (Newcomb et al, 2019; Seager van Dyk et al, 2024). Furthermore, the SGM-specific link between low family support, increased homestay, and lower mood underscores the need for designing and testing interventions that are accessible from within potentially nonaffirming home environments, such as online support programs (Bauermeister et al, 2022; Egan et al, 2021; Lucassen et al, 2015).…”
Section: Discussionmentioning
confidence: 99%